THU0520 DIFFUSE ENTHESITIS AND LOW-GRADE INFLAMMATION IN PATIENTS WITH METABOLIC SYNDROME: A CLINICAL AND ULTRASOUND STUDY. (2nd June 2020) - Falsetti, P.; Conticini, E.; Baldi, C.; Bardelli, M.; Gentileschi, S.; Cantarini, L.; Frediani, B.
Abstract : Background: Metabolic syndrome (MS) is a clinical condition characterized by central obesity and additional factors such dyslipidemia, hypertension, raised fasting plasma. Scanty observations describe the association of MS with musculoskeletal conditions, such as enthesopathies and diffuse idiopathic hyperostosis syndrome (DISH). Musculoskeletal ultrasound (US) has been applied to the study of entheses, but the real prevalence and characteristics of entheseal involvement in MS has yet to be clarified. Objectives: The aim of our work was to study the US-defined entheseal changes in MS, to correlates the US enthesitis scores to clinical characteristics, and to define a relation between MS-related enthesitis and the presence of concurrent DISH Methods: Sixty consecutive outpatients (24 males, 36 females, mean age 60 years), all fullfilling International Diabetes Foundation (IDF) criteria for MS, were also evaluated with multi-site bilateral US entheseal examination. Each patient underwent power Doppler (PD) US examination of twelve entheseal sites, using Esaote MyLab Twice with 6–18 MHz transducer. Enthesitis was defined on the basis of OMERACT's filter. Inflammatory and structural changes were scored as a whole when present (score 1) or absent (score 0). The sum of entheses with inflammatory and structural damage was defined as "global inflammatory score" (GIs) and "global structural damage score" (GSDs) for each patient. The Leeds Enthesitis Index (LEI) was also applied, and a spinal radiography was obtained for each patient to research concurrent signs of DISH satisfying Resnick and Niwayama criteria. Results: Patients showed moderate overweight (mean BMI 29) and a diagnosis of type 2 diabetes was present in 24 (40%). A low-grade inflammatory state was demonstrated in MS (mean CRP 0, 58 md/dL, mean ESR 21, 9 mm/h). A high prevalence of US-defined enthesitis was noted in 52 patients (86%) and 127/720 entheses (17, 6%). PD signals, were reported in 11 patients (18%) and 11/720 entheses (1, 52%), and they were associated to clinical symptoms expressed as LEI (p=0, 0138). Erosions, although rare (0.3% of entheses), were more frequent in males (p= 0.001). Moreover, in 57 patients (95%) and 217 entheses (30%) structural damages were found. A correlation was found between GIs and GSDs and both BMI (p=0.0233 and p=0.0068 respectively), LEI (p=0.03 and p=0.0099 respectively), and type 2 diabetes (p=0.0248 and p=0.0156 respectively). In 28 patients (46%) a concurrent diagnosis of DISH was made. In multivariate regression analysis the best predictors for DISH were higher levels of CRP (p=0, 038) and older age (p<0, 0001). DISH correlated with older age (p<0, 0001), CRP and ESR (p= 0, 0428 p=0, 0069 respectively) and US global scores for enthesitis (p=0, 0312 for GIs, p=0, 0071 for GSDs). Conclusion: This is the first study where diffuse enthesitis and entheseal structural damage are demonstrated with high prevalences in MS, comparable or also higher than those reported for SpA-related enthesitis. Our data, obtained using the most recent OMERACT's definition for US-detected enthesitis (proposed for SpA), also suggest a low specificity of this definition, in consideration of the high prevalence of MS-associated enthesitis. Moreover PD was associated to entheseal pain expressed as LEI. Both GIs and GSDs showed a correlation with overweight and type 2 diabetes. As secondary result, this study demonstrated that almost half of patients with MS could have a concurrent diagnosis of DISH. Patients with DISH were older, with higher levels of inflammation, and higher scores of US-defined enthesitis. Our results suggest that MS and DISH could be strictly related; diffuse enthesitis with a low-grade inflammatory state should be regarded as potential factor of progression from MS towards a conclamed DISH. Disclosure of Interests: None declared